Analisis Pemanfaatan Digital Fundraising Sebagai Strategi Mengoptimalkan Penghimpunan Zakat penghasilan Pada Baznas DKI - Annisa Maharani (2022)
Along with the rapid development of digital technology, activities of zakat fund collection has also innovated to utilize digital channels to increase the amount of zakat fund collection. Profession zakat is one of zakat type that collected from someone's income, which until now has not realized the realization of the collection in accordance with the existing potential. In order to increase profession zakat collection, Baznas as a national-level zakat management institution has also innovated in utilizing digital transformation in this things. A strategy is also needed to continue to optimize profession zakat collection by utilizing the role of digital transformation. The purpose of this study was to analyze how the use of digital fundraising in collecting profession zakat funds at Baznas DKI, as well as to find out how the strategy was carried out by Baznas DKI to continue to optimize profession zakat collection in utilizing digital fundraising. The method used in this research is qualitative with a case study approach. The expected result of this research is the pattern of using digital fundraising in Baznas DKI which is already good and can collect profession zakat funds according to the existing potential.